A Bourdieuan Relational Perspective for Entrepreneurship Research. (29th August 2014) - Tatli, Ahu; Vassilopoulou, Joana; Özbilgin, Mustafa; Forson, Cynthia; Slutskaya, Natasha; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> In this paper, we illustrate the possibilities a relational perspective offers for overcoming the dominant dichotomies (e.g., qualitative versus quantitative, agency versus structure) that exist in the study of entrepreneurial phenomena. Relational perspective is an approach to research that allows the exploration of a phenomenon, such as entrepreneurship, as irreducibly interconnected sets of relationships. We demonstrate how Pierre Bourdieu's concepts may be mobilized to offer an exemplary toolkit for a relational perspective in entrepreneurship research.